1991
DOI: 10.1002/nur.4770140309
|View full text |Cite
|
Sign up to set email alerts
|

Nurse burnout: Work related and demographic factors as culprits

Abstract: This study was an examination of the combined ability of perceived work environment, demographic, and work-related variables to predict burnout among 314 nurses at a large metropolitan hospital. The three dimensions of burnout measured were emotional exhaustion, depersonalization, and personal accomplishment. High work pressure and low work involvement and supervisor support predicted emotional exhaustion. Task orientation, work pressure, work involvement, and age predicted both depersonalization and personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 8 publications
0
36
0
2
Order By: Relevance
“…Frequent exposure to similar types of patients leads to outcomes that are familiar to the caregiver (Bobay, Gentile, & Hagle, 2009). This research would suggest that older and more experienced clinical ladder nurses would show greater leadership behaviors, although the literature on burnout could argue that older and experienced nurses who do not advance in organizations might demonstrate fewer leadership behaviors and decreased feelings of personal accomplishments (Kovacs, Kovacs, & Hegedus, 2010;Robinson et al, 1991).…”
Section: Clinical Ladder Programsmentioning
confidence: 97%
“…Frequent exposure to similar types of patients leads to outcomes that are familiar to the caregiver (Bobay, Gentile, & Hagle, 2009). This research would suggest that older and more experienced clinical ladder nurses would show greater leadership behaviors, although the literature on burnout could argue that older and experienced nurses who do not advance in organizations might demonstrate fewer leadership behaviors and decreased feelings of personal accomplishments (Kovacs, Kovacs, & Hegedus, 2010;Robinson et al, 1991).…”
Section: Clinical Ladder Programsmentioning
confidence: 97%
“…Empirical evidence from research on nurses found job satisfaction to be linked to several aspects of job performance, including: patient satisfaction (Krugman and Preheim, 1999), overall job performance (Judge et al, 2001), turnover; productivity (Butler and Parsons, 1989;Robinson et al, 1991).…”
Section: Performance and Job Satisfactionmentioning
confidence: 99%
“…Another occupational risk factor is a demanding and stressful work environment (O'Doherty, 1991;Piazza & Moal, 1998;Robinson et al, 1991). Nurses in this study talked extensively about the stressful work environment to which they were consistently exposed.…”
Section: Personal and Professional Stressorsmentioning
confidence: 97%